2012
DOI: 10.1111/j.1463-1318.2012.02992.x
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous resection of colorectal cancer and liver metastases: comparative views of colorectal and liver surgeons

Abstract: Although significant concerns relating to synchronous resection remain amongst colorectal and liver surgeons, a majority of them felt that synchronous resections could be offered to appropriately selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…Two studies report a delay of about 4 months between liver and rectal surgery in patients undergoing the liver-first approach in which long-course radiotherapy was delivered after liver surgery [14,17]. In the study period our institution had significant concerns performing a liver resection at the same time as a major complex rectal resection, in line with a 2012 review of colorectal and liver surgeons in Great Britain [21]. Conversely, since 55% of the liver resections in the current study were minor wedge resections, simultaneous resection of the rectal cancer and liver metastases in these cases might have been an even more efficient treatment algorithm [7].…”
Section: Discussionmentioning
confidence: 89%
“…Two studies report a delay of about 4 months between liver and rectal surgery in patients undergoing the liver-first approach in which long-course radiotherapy was delivered after liver surgery [14,17]. In the study period our institution had significant concerns performing a liver resection at the same time as a major complex rectal resection, in line with a 2012 review of colorectal and liver surgeons in Great Britain [21]. Conversely, since 55% of the liver resections in the current study were minor wedge resections, simultaneous resection of the rectal cancer and liver metastases in these cases might have been an even more efficient treatment algorithm [7].…”
Section: Discussionmentioning
confidence: 89%
“…Colorectal cancer is the second most common cause of cancer‐related deaths in the United States and in the United Kingdom . The most common metastatic site is the liver , with 15–25% of patients having colorectal liver metastasis (CLM) at the time of diagnosis , and another 30–50% of patients developing CLM during their treatment course .…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneous resection removes all tumour burdens in one operation and it permits the prompt commencement of adjuvant chemotherapy. Furthermore, it avoids the hepatotoxic side effects of neoadjuvant chemotherapy, which means that simultaneous resection is a safer operation with lesser risk of post-operative liver failure and complications (14)(15)(16)(17). However, some medical facilities do not recommend simultaneous resection if simultaneous resection is needed to treat rectal cancer or in patients undergoing extensive liver resection because it may increase the risk of perioperative complications (14).…”
mentioning
confidence: 99%
“…Furthermore, it avoids the hepatotoxic side effects of neoadjuvant chemotherapy, which means that simultaneous resection is a safer operation with lesser risk of post-operative liver failure and complications (14)(15)(16)(17). However, some medical facilities do not recommend simultaneous resection if simultaneous resection is needed to treat rectal cancer or in patients undergoing extensive liver resection because it may increase the risk of perioperative complications (14). Although several studies have demonstrated the safety of simultaneous liver resection for CRLM, these studies did not evaluate the outcomes of simultaneous liver resection depending on the primary tumor location and type of liver resection (major or minor).…”
mentioning
confidence: 99%